Case Report: First Occurrence of Plasmablastic Lymphoma in Activated Phosphoinositide 3-Kinase δ Syndrome - Yin, Zexi; Tian, Xin; Zou, Runying; He, Xiangling; Chen, Keke; Zhu, Chengguang (Frontiers in Immunology, 2021)
Activated phosphoinositide 3-kinase δ syndrome (APDS) is an autosomal dominant primary immunodeficiency caused by acquired gene function mutation (GOF).APDS has a variety of clinical phenotypes, particularly recurrent respiratory infections and lymphoproliferation. Here we report a pediatric patient with APDS who presented with recurrent respiratory infections, lymphoproliferation, hepatosplenomegaly, bronchoscopy suggesting numerous nodular protrusions in the airways and a decrease in both T and B lymphocytes, and progression to plasmablastic lymphoma (PBL) after 1 year. Whole exome sequencing revealed a heterozygous mutation in the PIK3CD gene (c.3061 G>A p.E1021K). This is the first reported case of APDS combined with PBL and pediatricians should follow up patients with APDS regularly to be alert for secondary tumours.